Gundestrup and Titelberg - Sander-Jørgensen Rowlett , Elsebeth; M. Rowlett, Ralph (Hikuin, 1984)
The great silver cauldron found in Gundestrup’s Rævemose in Himmerland may originally have been used for Iron Age ritual, but today it has become a pressure cooker for generating hypotheses. There persists a considerable difference of opinion as to the meaning of the pictorial panels, with an even wider assortment of suggestions as to its place of manufacture.